REST and Its Corepressors Mediate Plasticity of Neuronal Gene Chromatin throughout Neurogenesis - Ballas, Nurit; Grunseich, Christopher; Lu, Diane D.; Speh, Joan C.; Mandel, Gail (Cell, 2005)
Regulation of neuronal gene expression is critical to central nervous system development. Here, we show that REST regulates the transitions from pluripotent to neural stem/progenitor cell and from progenitor to mature neuron. In the transition to progenitor cell, REST is degraded to levels just sufficient to maintain neuronal gene chromatin in an inactive state that is nonetheless poised for expression. As progenitors differentiate into neurons, REST and its corepressors dissociate from the RE1 site, triggering activation of neuronal genes. In some genes, the level of expression is adjusted further in neurons by CoREST/MeCP2 repressor complexes that remain bound to a site of methylated DNA distinct from the RE1 site. Expression profiling based on this mechanism indicates that REST defines a gene set subject to plasticity in mature neurons. Thus, a multistage repressor mechanism controls the orderly expression of genes during development while still permitting fine tuning in response to specific stimuli.